Earthquake Disaster Preparedness for Students of Junior High School - Leo Widdyusuf; M Muktiarni; Jonah Mupita (ASEAN Journal of Science and Engineering Education, 2022)
Disaster preparedness is one of the actions to reduce the impact of disasters, especially earthquakes. One of the locations that has a risk of fatalities is the school. This study aims to determine the level of knowledge of students regarding student preparedness in an earthquake disaster and provide guidance. This research was conducted using quantitative descriptive techniques and primary data collection techniques random sampling obtained from 102 student respondents. From the comparison of the pre-test and post-test, the students showed an increase in grades that had entered the good category with an average percentage of students above 70%. This happened because of the provision of earthquake disaster preparedness materials to the students. The results showed that the level of knowledge students in preparedness for earthquake natural disasters was in good category.